2011
DOI: 10.3324/haematol.2011.051938
|View full text |Cite
|
Sign up to set email alerts
|

Membrane microdomain sphingolipids are required for anti-CD20-induced death of chronic lymphocytic leukemia B cells

Abstract: The lipid organization of membranes of B cells from patients with chronic lymphocytic leukemia differs from one patient to another. In practice, given the relevance of the membrane lipid distribution to the efficacy of biotherapies, this observation is of potential importance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…Next we compared CD20 (target antigen), GM1 and sphingomyelin (lipid raft markers) in vitro expression between the two patient groups as the ability of CD20 to translocate into lipid rafts is suspected to be important for complement activation by anti-CD20 mAb [ 31 ], and that lipid raft integrity may be compromised in CLL cells [ 25 , 26 , 32 ] (Figure 3A and Table 2 ). No differences were observed when comparing in both groups (i) the numbers of CD20 molecules between groups; (ii) the mean fluorescence intensity (MFI) of the FITC-conjugated cholera toxin subunit B recognizing GM1; and (iii) the MFI of lysenin-bound-sphingomyelin.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Next we compared CD20 (target antigen), GM1 and sphingomyelin (lipid raft markers) in vitro expression between the two patient groups as the ability of CD20 to translocate into lipid rafts is suspected to be important for complement activation by anti-CD20 mAb [ 31 ], and that lipid raft integrity may be compromised in CLL cells [ 25 , 26 , 32 ] (Figure 3A and Table 2 ). No differences were observed when comparing in both groups (i) the numbers of CD20 molecules between groups; (ii) the mean fluorescence intensity (MFI) of the FITC-conjugated cholera toxin subunit B recognizing GM1; and (iii) the MFI of lysenin-bound-sphingomyelin.…”
Section: Resultsmentioning
confidence: 99%
“…No differences were observed when comparing in both groups (i) the numbers of CD20 molecules between groups; (ii) the mean fluorescence intensity (MFI) of the FITC-conjugated cholera toxin subunit B recognizing GM1; and (iii) the MFI of lysenin-bound-sphingomyelin. As we have previously observed that sphingomyelin overexpression in CLL cells induced by rifampicin affects the type II anti-CD20 mAb (B1) capacity to kill CLL cells [ 32 ], the experiment was repeated with RTX instead of B1 (tositumomab), revealing that sphingomyelin overexpression had no effect on the RTX capacity to induce CDC (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Specific changes in the composition and metabolism of GSLs occur during cell proliferation, cell cycle phases, brain development, differentiation, and neoplasia in various cell types, indicating that the ganglioside composition responds to changes in the morphology and function of cells [43]. Hammadi et al showed that B cells are diverse from one CLL patient to another with respect to their membrane lipid organization [11]. In particular, they observed that CLL B cells were characterized by high GM1 gangliosides and SM (Sphingomyelin) levels in their plasma membrane, they possessed active P-gp (Pglycoprotein) pumps, recruited Cbp (Csk-binding protein), and ultimately they were sensitive to B1 mAb-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%